Direct or Indirect Action Mechanisms of Naringin in Maintaining Bone Homeostasis: Naringin Maintaining Bone Homeostasis - Zhao, Xianghu; Hu, Jing; Liu, Jie; Meng, Yi; Liu, Xiangzhong; Xu, Haijia; Ning, Yu; Li, Zhanghua (Cellular and Molecular Biology, 2023)
Disruption of bone homeostasis is the pathological basis of bone diseases. Multiple cells work together to maintain homeostasis and bone health. As a natural flavonoid compound, Naringin (NG) can positively affect the maintenance of bone homeostasis by acting on different types of cells. In this review, we discuss the direct and indirect osteoprotective effects of NG as well as the underlying mechanisms, and we provide a critical perspective on its clinical translation.